Tumbuhan Berpotensi Bahan Pangan di Desa Sebangun Kecamatan Sebawi Kabupaten Sambas - Riza Linda, Yeni Nurhidayah, Irwan Lovadi (Jurnal Protobiont, 2015)
Sebangun village, Sebawi Sub-district, Sambas Regency whose residents are all ethnic Malays have a diversity of potential-food plant. Ethnic Malays in Sambas have a culture of utilizing plants for fulfilling their food needs, for example â€œmerandauâ€. Ethnobotanical studies needs to be conducted to explore the plant that serve as potential food in the village. This research aims to identify the types of potential-food plant in Sebangun village; part that are used; utilization categories; and method of preparation, as well as to determine thr citation frequency value and the informant agreement ratio (IAR). The research used were purposive sample and semi-structured interviews. Quantitative analysis in the study was conducted for the citation frequency, the informant agreement ratio (IAR) and the percentage of the habits and parts of potential-food plant. Thirty three species of potential-food plant categorized into twenty four familis were found in this research. The fruit was the most widely utilized as food. The plant mostly used as potential food fell into the category og utilization as vegetables, i.e. fifteen species of them. The highest value of the citation frequency in this research reached 100%. The category of utilization as vegetables received the highest informan agreement ratio (IAR), i.e. 0.930.